2018
DOI: 10.2217/rme-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Membrane as Differentiating Matrix for in Vitro Chondrogenesis

Abstract: Aim: The aim of the present study is to use human amniotic membrane (HAM) for in vitro chondrogenesis of placenta-derived mesenchymal stem cells (MSCs) and umbilical cord-derived MSCs. Materials & methods: MSCs from the placenta and umbilical cord were isolated, characterized by immunophenotyping and after analyzing their rate of proliferation, cytotoxicity and viability, chondrogenesis was performed on plastic adherent surface and on HAM. Results: Successfully isolated and characterized placenta-derived M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…We analyzed the cytocompatibility of both, the epithelial and basal sides of D-hAM with hUC-MSC separately. Consistent with earlier studies, 23,25,61 hUC-MSC remained viable and proliferated actively on D-hAM for up to 15 days in culture. Moreover, the present study showed that hUC-MSC seeded on the basal side of D-hAM presented significantly higher proliferation on the basal surface than the epithelial surface, which is a relatively novel finding.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We analyzed the cytocompatibility of both, the epithelial and basal sides of D-hAM with hUC-MSC separately. Consistent with earlier studies, 23,25,61 hUC-MSC remained viable and proliferated actively on D-hAM for up to 15 days in culture. Moreover, the present study showed that hUC-MSC seeded on the basal side of D-hAM presented significantly higher proliferation on the basal surface than the epithelial surface, which is a relatively novel finding.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, several previous studies have shown that MSCs attach to and proliferate in the D-hAM. [23][24][25] However, the compatibility of the two surfaces of the D-hAM with MSCs have not been compared. Therefore, the objectives of this study were to investigate the effect of decellularization on the proteomic profile of decellularized hAM (D-hAM) prepared by a salt-based decellularization process using LC-MS/MS and determine the comparative compatibility of the two surfaces of D-hAM with human umbilical cord mesenchymal stem cells (hUC-MSC).…”
Section: Introductionmentioning
confidence: 99%
“…Immunocytochemistry was performed by the previously established protocol in stem cell lab 16 . CD73 (41–0200 Invitrogen, USA), CD90 (MA1‐35307 Invitrogen, USA) and CD105 (MA5‐17041 Invitrogen, USA) and negative markers CD34 (11–0341‐82 Invitrogen, USA), CD45 (MA1‐7654 Invitrogen, USA) were used in particular dilutions.…”
Section: Methodsmentioning
confidence: 99%
“…reported the potential of decellularized AM basement membrane to support proliferation and differentiation of umbilical cord-derived MSCs (UC-MSCs) and placenta-derived MSCs (P-MSCs) into chondrocyte-like cells [49]. Khorramirouz et al also demonstrated the ability of decellularized AM to support AT-MSCs differentiation into cardiomyocytes when applied as a cardiac patch for the treatment of acute myocardial infarction in rat models [50].…”
Section: Amniotic Membranementioning
confidence: 99%